The Effects of Reference Pricing on Housing Market: Evidence from Shenzhen China - Arestis, Philip; Lai, Mianshan; Hou, Jia (Panoeconomicus, 2023)
This paper investigates an unprecedented regulation measure in the housing market, reference pricing, with evidence from Shenzhen China. We use a unique panel dataset, obtained through questionnaires to real estate agents, to document the effects of the policy on the housing market. The hypotheses that trading volume and house price decrease are validated by the data, while the one that turnover time increases is not supported. We discuss potential mechanisms that may explain these effects. Meanwhile, we infer estate-level discount factors that are not public information. Based on these factors, we forecast reference prices for the subsequent year. Overall, this paper fills the gap in the field of reference pricing effects on the housing market. JEL: R31, O18, E64